COURAGE AND MODESTYAS THE ATTRIBUTES OF MORAL VALUE IN THE NOVEL OF THE OLD MAN AND THE SEA - Aristiawan, Danul (JOLLT Journal of Languages and Language Teaching, 2020)
The aim of the research was to analyze the courage and modesty as the attributes of moral value in The Old Man And The Sea. This research was descriptive qualitative research. The data were words, phrases, sentences or fragments from the first until the last chapters. The result of this research were: (1)Santiago?s being determined, being hard-working and perseverance, and optimistic of what he did (2)The attribute of being modest or modesty was displayed in various characteristics of Santiago. Some characteristics of Santiago were being unselfish, care, respect, loving, feeling lonely, sympathetic, and even feeling of regretful after killing a fish. The attribute of being modest was displayed by showing that the old man behaves as if he were the father of the young boy Manolin. In terms of being religious, the old man displayed the characteristic of being grateful to God when he realized that God had made the fish not as intelligent as human. This, in the old man?s view, made it possible that human could kill the fish. In such a feeling, he also imagined if only the fish were as intelligent as human. This novel revealed the Courage and Modesty in details.